Three-dimensional bulk electronic structure of the Kondo lattice CeIn3 revealed by photoemission - Zhang, Yun; Lu, Haiyan; Zhu, Xiegang; Tan, Shiyong; Liu, Qin; Chen, Qiuyun; Feng, Wei; Xie, Donghua; Luo, Lizhu; Liu, Yu; Song, Haifeng; Zhang, Zhengjun; et al. (Scientific reports, 2016)
We show the three-dimensional electronic structure of the Kondo lattice CeIn 3 using soft x-ray angle resolved photoemission spectroscopy in the paramagnetic state. For the first time, we have directly observed the three-dimensional topology of the Fermi surface of CeIn 3 by photoemission. The Fermi surface has a complicated hole pocket centred at the Γ-Z line and an elliptical electron pocket centred at the R point of the Brillouin zone. Polarization and photon-energy dependent photoemission results both indicate the nearly localized nature of the 4 f electrons in CeIn 3 , consistent with the theoretical prediction by means of the combination of density functional theory and single-site dynamical mean-field theory. Those results illustrate that the f electrons of CeIn 3 , which is the parent material of CeMIn 5 compounds, are closer to the localized description than the layered CeMIn 5 compounds.